Defining, Measuring, and Benchmarking Administrative Expenditures of Mandatory Social Security Programs - Sluchynsky, Oleksiy (World Bank, Washington, DC, 2015)
This study provides a framework for comparison and benchmarking of administrative expenditures of public and private social security programs. The paper presents the genesis of the inquiries into the subject, reviewing some of the most relevant literature on administrative expenditures and the costs of mandatory programs produced over the past two decades. The quantitative analysis builds on the extensive body of literature, but our framework evolved considerably from earlier studies. Our dataset includes over 100 observations and a broad set of explanatory variables. The authors developed and compared a number of standardized cost indices discussing their advantages and limitations. The author also discusses major cost components and their shares in total program costs. The analysis explains over 90 percent of variation in administrative expenditures. It confirms some of the hypotheses expressed in the earlier studies and presents new evidence of driving factors for costs. The author developed three different specifications for statistical analysis. The first set looks at the impact of design of a program on total costs. The second group of specifications assesses differences in costs of managing pension liabilities between the public and private mandatory pension schemes. Finally, on the basis of the third model the author generate benchmarks for staffing levels and for the total administrative expenditures. The author compares those to the actual indicators and develops standard performance ratios, providing insights into design variations and performance of the programs. The author concludes with a discussion of data limitations and implications of our findings.